Magnetic field dependence of conductivity and effective mass of carriers in a model of Mott-Hubbard material - Didukh, L.; Kramar, O.; Skorenkyy, Yu.; Dovhopyaty, Yu. (Condensed Matter Physics, 2005)
The effect of external magnetic field h on a static conductivity of MottHubbard
material which is described by the model with correlated hopping
of electrons has been investigated. By means of canonical transformation,
the effective Hamiltonian is obtained which takes into account strong
intra-site Coulomb repulsion and correlated hopping. Using a variant of
generalized Hartree-Fock approximation the single-electron Green function
and quasiparticle energy spectrum of the model have been calculated.
The static conductivity σ has been calculated as a function of h, electron
concentration n and temperature T . The correlated hopping is shown to
cause the electron-hole asymmetry of transport properties of narrow band
materials В статтi досліджено вплив зовнішнього магнiтного поля на статичну
провідність Мотт-Габбардiвського матеріалу в моделi з корельованим переносом електронів. Ефективний гамiльтонiан отримано iз
застосуванням канонічного перетворення та з використанням узагальненого наближення Гартрi-Фока знайдено функцію Грiна i енергетичний спектр. Провідність розрахована як функція магнiтного поля, концентрації електронів та температури.